Two new monobasic thrips genera for a gall-inducing species and its kleptoparasite (Thysanoptera, Phlaeothripinae) - Mound, Laurence A.; Wells, Alice (Zootaxa, 2020)
Drypetothrips korykis gen. et sp.n. is described as inducing leaf-margin galls on a small tree in Australia, Drypetes deplanchei [Putranjivaceae]. This thrips is similar in appearance to the smaller species of the genus Kladothrips that induce galls on Acacia species. The galls are invaded by a phytophagous kleptoparasitic thrips, Pharothrips hynnis gen. et sp.n., females of which have a forked plough-like structure protruding ventrally on the frons that is unique amongst Thysanoptera.